2008
DOI: 10.1152/ajpendo.90296.2008
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage infiltration into adipose tissue may promote angiogenesis for adipose tissue remodeling in obesity

Abstract: The biological role of macrophage infiltration into adipose tissue in obesity remains to be fully understood. We hypothesize that macrophages may act to stimulate angiogenesis in the adipose tissue. This possibility was examined by determining macrophage expression of angiogenic factor PDGF (platelet-derived growth factor) and regulation of tube formation of endothelial cells by PDGF. The data suggest that endothelial cell density was reduced in the adipose tissue of ob/ob mice. Expression of endothelial marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
148
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(159 citation statements)
references
References 55 publications
9
148
0
2
Order By: Relevance
“…As a major hypoxia-responsive gene, the protein abundance of HIF1␣ and its transcriptional activity in adipose tissue are elevated in obese adipose tissue (7,11,26). It has been postulated that local hypoxia instigates macrophage infiltration and inflammation in obese adipose tissue through activation of HIF1␣ (34). Indeed, a recent report from Scherer and colleagues (26) demonstrates that transgenic expression of a constitutively active form of HIF1␣ induces fibrosis and inflammation in WAT, leading to impaired glucose tolerance in mice.…”
Section: Discussionmentioning
confidence: 99%
“…As a major hypoxia-responsive gene, the protein abundance of HIF1␣ and its transcriptional activity in adipose tissue are elevated in obese adipose tissue (7,11,26). It has been postulated that local hypoxia instigates macrophage infiltration and inflammation in obese adipose tissue through activation of HIF1␣ (34). Indeed, a recent report from Scherer and colleagues (26) demonstrates that transgenic expression of a constitutively active form of HIF1␣ induces fibrosis and inflammation in WAT, leading to impaired glucose tolerance in mice.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,38 We postulated, therefore, that 14S,21R-diHDHA enhances the functions of db/db macrophages in angiogenesis, in part, by increasing their angiogenic cytokine production. The results demonstrated that lesser amounts of VEGF and PDGF-BB were released by db/db macrophages than by db/ϩ macrophages ( Figure 3, E and F), consistent with impaired functions of db/db macrophages.…”
Section: S21r-dihdha Recovers Impaired Prohealing Functions Of Macmentioning
confidence: 98%
“…35,36 Another developmental function of macrophages is the provision of trophic support. As potent effector cells, macrophages produce a range of mediators including plateletderived growth factors (PDGFs), 37 transforming growth factors (TGFs), 38 insulin-like growth factor (IGF)-1 39 and Wnts. [40][41][42] Macrophage-derived factors mediate cell fate decisions, as observed in β cell differentiation in the developing pancreas 43 and hepatic progenitor differentiation during liver regeneration.…”
Section: Ontogeny Of Embryonic Macrophagesmentioning
confidence: 99%
“…40 Macrophages also contribute to development through angiogenic regulation. 30 In addition to the production of a range of pro-and anti-angiogenic factors, 36,37,42 macrophages have been shown to assist in vascular patterning by physically directing angiogenic positioning.…”
Section: Ontogeny Of Embryonic Macrophagesmentioning
confidence: 99%